Life cycle assessment of global warming potential, resource depletion and acidification potential of fossil, renewable and secondary feedstock for olefin production in Germany. (20th March 2020) - Keller, Florian; Lee, Roh Pin; Meyer, Bernd
Abstract: Lower olefins are the second most resource and emission intensive products in the manufacturing sector in Germany. Replacing conventional fossil feedstock with renewable or secondary feedstock thus represents a viable possibility to significantly increase the sustainability of the German industry. The environmental impact associated with olefin production is generally determined by feedstock and energy supply as well as the production technology. In the present study, the environmental effects of the utilization of conventional and alternative feedstock are assessed in the form of a cradle-to-gate life cycle assessment performed in GaBi LCA software. The assessment focused on global warming potential, fossil resource depletion and acidification potential of olefin production in Germany. Investigated raw materials included fossil resources in crude oil and shale gas, renewable resources in wood and maize-based biogas as well as secondary resources in municipal solid waste and flue gas-based carbon dioxide. Life cycle inventory data for olefin production are obtained by process simulation using Aspen Plus. Technologically, syngas-based olefin production is characterized by a lower product carbon recovery compared to direct cracker-based olefin production. By integrating upstream impacts, renewable-based production is observed to lead to negative effective greenhouse gas emissions and low resource demand, but showed significant acidification potential from agricultural feedstock production. Due to the avoidance of waste incineration, olefin production via waste gasification is associated with significant benefits in terms of greenhouse gas emissions, despite the substitution of waste-based electricity generation with other energy sources. The utilization of carbon dioxide from flue gas displayed the highest electricity demand by means of hydrogen generation. Therefore, a high level of renewable energy integration is required to be environmentally viable. Highlights: Olefin feedstock alternatives are evaluated in a cradle-to-gate LCA in GaBi. Global warming, fossil resource depletion and acidification are assessed. Feedstock included crude oil, shale gas, wood, maize, solid waste and flue gas. Inventory data for olefin production are provided by process simulation in Aspen Plus.